2020
DOI: 10.1371/journal.pone.0228921
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum interleukin-17A and interleukin-18 levels in patients with type 2 diabetes mellitus with and without periodontitis

Abstract: Objective Interleukin (IL)-17A and IL-18 have been proposed to play important roles in periodontitis and type 2 diabetes mellitus (DM), but human data are conflicting. The present study aimed to investigate the roles of IL-17A and IL-18 in periodontitis and DM by measuring salivary and serum levels, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Despite this function being co-aligned with the pathophysiology of PD (biofilm challenge in the periodontal pocket), in reality, the relationship between IL-17A and PD remains complex and unclear, with evidence to suggest both protective and destructive effects 65 . Previous cross-sectional studies assessing local production of IL-17A in the gingival crevicular fluid (GCF) and saliva have been largely incolclusive, with some studies reporting higher levels in PD 66 , 67 , whilst others find higher levels in PH 68 , 69 . Another study reported elevated levels in localised PD compared with generalised PD and PH, suggesting that IL-17A may peak in early gingival inflammation rather than established periodontitis 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this function being co-aligned with the pathophysiology of PD (biofilm challenge in the periodontal pocket), in reality, the relationship between IL-17A and PD remains complex and unclear, with evidence to suggest both protective and destructive effects 65 . Previous cross-sectional studies assessing local production of IL-17A in the gingival crevicular fluid (GCF) and saliva have been largely incolclusive, with some studies reporting higher levels in PD 66 , 67 , whilst others find higher levels in PH 68 , 69 . Another study reported elevated levels in localised PD compared with generalised PD and PH, suggesting that IL-17A may peak in early gingival inflammation rather than established periodontitis 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Salivary levels of IL-18 were found to be 5-fold higher in patients with periodontitis than healthy ones (Banu et al 2015). In another recent study, salivary IL-18 levels were not different between patients with and without periodontitis; however, salivary IL-18 was positively associated with fasting plasma glucose, and serum IL-18 levels were correlated with HbA 1C (Techatanawat et al 2020).…”
Section: Il-18mentioning
confidence: 91%
“…The studies included were conducted in India, 2,19-25 Brazil, [26][27][28] Ukraine, 29 Iran, 30 Indonesia, 31 and Thailand. 32 All the articles were published in English, except the Ukrainian study, which was translated into English using the DeepL online translator (Köln, Germany) before the analysis was performed.…”
Section: Location Of the Studiesmentioning
confidence: 99%
“…21,22,29 The appropriate statistical analysis was not detailed in four studies. 21,22,29,31 Among the studies evaluated, nine were classified as high quality, 2,19,20,23,[25][26][27][28]32 four, as low quality, 21,22,24,29 and two, as medium quality. 30,31 The risk of bias assessments can be accessed at https:// osf.io/a53bc/files/.…”
Section: Data Analysis and Presentationmentioning
confidence: 99%